The influence of the arabic conquests on a linguistic situation in Sicily - Seredina, Aleksandra Yuryevna; Mukhametshina, Evelina Erkenovna; Kalegina, Tatiana Evgenievna (Universidade Estadual Paulista, 2021)
This article is devoted to the study of the Italian language vocabulary, as well as its enrichment with Arabic borrowings under the influence of various historical events in the course of the historical development of the island of Sicily. The authors describe the main historical events that influenced the enrichment of the lexical composition of the Italian language with Arabic borrowings. The history of the Mediterranean is saturated with conflicts, meetings, migrations. For centuries, the region of southern Italy has been the center of various cultures and peoples, which greatly influenced the development of art and architecture as well as vocabulary of the people living in this territory. The purpose of the study is to describe and analyze the lexemes of Arabic origin present in the Italian language and Sicilian dialects. The lexemes are referred to "arabisms" that emerged during the period of Arab domination in the southern Italy and under the influence of the Arabic language. Within the scope the authors consider in detail the most important historical events that took place in certain periods in the region. In addition, the authors overview the semantic fields in which there are arabisms and the areas they are related, e.g. toponymy, material culture, agriculture, manufacturing, food, etc. Also the geography of the region and the linguistic contacts are regarded due to the conquests of the Arabs in Sicily.